Optimalisasi Metode Diskusi dalam Interpretasi Puisi â€œBila Kutitipkanâ€ Karya Ahamad Mustofa Bisri - Saifullah, Saifullah; Lanta, Jumiati; Rasyid, Rustam Efendy; Kasman, Rosmini; Ecca, Suleha; Karina, Karina (Nuances of Indonesian Language, 2023)
The aim of this study is to determine the ability of the 10th-grade students at State Senior High School 1 Sidrap to interpret the poem "Bila Kutitipkan" by Ahmad Mustofa Bisri and the factors influencing students' ability to interpret poetry. The sample for this research consists of 30 students. The research was conducted on September 18, 2023, at State Senior High School 1 Sidrap. The data collection method used was group discussions. The data was analyzed using frequency tables. Based on the research results, it was found that 24 students scored above 75, with a percentage of 80%, and 6 students scored below 75, with a percentage of 20%. Based on the data above, it can be concluded that 10th-grade students at State Senior High School 1 Sidrap are capable of interpreting the poem "Bila Kutitipkan" by Gus Mus. There are three factors influencing students' ability to interpret poetry: the frequency of reading poetry, the enjoyment of reading poetry, and the impact of poetry on students' lives. Based on the research results, out of the 30 students at State Senior High School 1 Pancarijang, 22 of them stated that they often and enjoy reading poetry, and poetry has an impact on their lives, while 8 students stated that they neither enjoy nor often read poetry, and poetry does not have an impact on their lives.Â